2014
DOI: 10.2135/cropsci2013.09.0585
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability of Certain Agronomic Traits in Quality Protein Maize under Stress and Nonstress Environments in Eastern and Southern Africa

Abstract: Growing maize (Zea mays L.) hybrids tolerant to drought and low‐nitrogen (N) stress would significantly reduce yield losses occurring in Africa. This study evaluated the performance of quality protein maize (QPM) F1 hybrids, and general (GCA) and specific combining ability (SCA) of QPM inbred lines for grain yield and other agronomic traits under stress and nonstress environments. A diallel cross of 15 QPM inbred lines was evaluated under drought and low‐N stresses and optimal conditions in a total of 17 envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
34
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 23 publications
17
34
2
1
Order By: Relevance
“…The mean squares due to GCA and SCA were highly significant for most traits. This finding is in line with previous diallel studies on QPM inbred lines (Pixley and Bjarnason, 1993;Bhatnagar et al, 2004;Wegary et al, 2011;Wegary et al, 2014). Significant GCA  environment interaction is an indication of variation in the GCA effects of lines under different environments, suggesting the need to select different parental lines for hybrid development at specific environments.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The mean squares due to GCA and SCA were highly significant for most traits. This finding is in line with previous diallel studies on QPM inbred lines (Pixley and Bjarnason, 1993;Bhatnagar et al, 2004;Wegary et al, 2011;Wegary et al, 2014). Significant GCA  environment interaction is an indication of variation in the GCA effects of lines under different environments, suggesting the need to select different parental lines for hybrid development at specific environments.…”
Section: Discussionsupporting
confidence: 90%
“…Mean performances of inbred lines, hybrids, high-parent heterosis, and general combining ability (GCA) values for grain yield (Mg ha −1 ), evaluated in the six environments. traits (Pixley and Bjarnason, 1993;Bhatnagar et al, 2004;Musila et al, 2010;Elmyhum, 2013;Wegary et al, 2014). Genotype-environment interactions were significant for most traits, resulting in rank differences of the genotypes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Musila et al (2010) reported the preponderance of additive gene action for grain yield, anthesis date, ASI and EPP in adapted early maturing QPM inbred lines evaluated under low-N, drought, and optimal environments. In contrast, Wegary et al (2013) reported GCA effects to be more important under drought, while SCA effects were more important under low-N and optimal conditions for grain yield. The differences in the results reported in the studies may be due to the fact that the inbred lines used in the different studies were derived from diverse germplasm sources and these might have had some genes with different modes of action (Badu-Apraku et al, 2013).…”
Section: Inheritance Of Grain Yield and Other Traits Of Early Maturinmentioning
confidence: 79%
“…This suggested that additive gene action for grain yield and other agronomic traits was the most important contributor to the heritable variation in agronomic traits in these genotypes. Results of other studies have indicated preponderance of additive over nonadditive gene action (Vasal et al, 1993a,b;Bhatnagar et al, 2004;Musila et al, 2010;Wegary et al, 2013). However, such important information is completely lacking on the gene action conditioning the grain yield of IITA's early QPM inbreds under drought, low-N or Striga infestation.…”
Section: Introductionmentioning
confidence: 98%